Pengaruh Ekstrak Bubuk Kakao (Theobroma cacao L.) pada Model Tikus Fase Retensi Ortodonti terhadap Peningkatan Ekspresi Kolagen Tipe I di Ligamen Periodontal - Daffa Rajendra (Fakultas Kedokteran Gigi, 2026)
Malocclusion is the third largest oral health problem in the world after caries and periodontal disease. The retention phase in orthodontic treatment requires a longer time to achieve optimal tissue stability. Cocoa powder extract (Theobroma cacao L.) is known to contain active compounds phenolic, flavonoid, and tannin which are thought to play a role in increasing type I collagen. Type I collagen is the main component of the extracellular matrix that plays a role in periodontal ligament remodeling so can reduce the risk of relapse. Method the study was conducted in vivo using experimental animals. Then, immunohistochemical staining techniques were performed and continued examination using a light microscope and ImageJ application. The results of this study showed that there was a significant difference in type I collagen expression between the control and treatment groups on days 3, 7, and 14 (p < 0.05). The significant increase in type I collagen expression in the treatment group is thought to be due to the content of bioactive compounds in cocoa powder extract (Theobroma cacao L.) which plays a role in increasing collagen 1 in the periodontal ligament. Further research using cocoa powder extract (Theobroma cacao L.) is needed to determine the effectiveness of bioactive compounds optimal periodontal ligament remodeling in the retention phase.
Finalisasi 1 Juli 2026_Yudi
Keywords: Cocoa powder extract; retention phase; type I collagen; periodontal ligament; relapse